MEMBANGUN PERADABAN MODERASI MELALUI KITAB RISALAH AHLUSSUNNAH WAL JAMAAH KARYA KH. HASYIM ASYARI - Taufiq Zaenal Mustofa; Akhmad Rifai (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
This literature research departs from the author's anxiety over the phenomenon of the rise of exclusivity in the religious life of the educated. The seeds of exclusivity can be seen from learning activities, extra-curricular activities, to the contents of textbooks. This anxiety is reinforced by the findings of a survey of credible research institutions. From this point, the writer is motivated to re-examine the treasures of moderating values contained in the works of classical scholars. The choice fell on the book of Risalah Ahlussunnah wal Jamaah by Shaykh Hasyim Asy'ari. This book became the research choice because Shaykh is a figure for Islamic moderatism in Indonesia. The purpose of this research is to elaborate on the values of moderation contained in the Risalah and make a simple contribution to counter-radicalism education in an educated society. This research is a type of qualitative research literature (library research) which examines the book of Risalah as the object of study. At the interpretation stage, the descriptive analysis or syarah. Descriptive analysis is an actual explanation of what is meant by a book text and paraphrasing it in the author's language. Based on the results of the study, it was found that there were at least fourteen values of moderation education contained in the Risalah. The fourteen values are: (1) Upholding the Prophetic Tradition (Sunnah), (2) Prioritizing unity over differences, (3) Accommodating local cultural traditions, (4) Prioritizing the public benefit, (5) Da'wah wisely and by example good, (6) Organized in carrying out goodness, (7) Oriented to religion and civilization, (8) Social empathy, (9) Adhering to the opinion of the mainstream/majority of scholars, (10) Proportionality in the use of ratios and revelations (aqli and naqli), (11) Giving importance to scientific genealogy (Sanad), (12) Obligation of taqlid for those who do not have the capacity for ijtihad, (13) Creating Mandubah Bid'ah (innovation and creativity), (14) Tradition of verification (tabayun) and stay away from hoax. The fourteen values are expected to be able to contribute to moderate thinking in the world of education and civilization.